Sistema de irrigação de baixa pressão e baixo custo para culturas em fileiras e adensadas - Xavier, Alyssandny Francisco Matos (Universidade Federal Rural do Semi-Árido, 2016)
The semi-arid to present unfavorable weather conditions for agriculture, with water deficit during most time of the year, poorly distributed rainfall and high temperatures, require irrigation for crop development. In the perspective of sustainable agriculture, drip irrigation is the method of more efficient use of water, which has attracted farmers and agricultural companies. Irrigation systems by gravity in closed conduits are the most suitable for family farmers, due to low cost and operate at low pressures. This study aimed to develop a similar irrigation system to the bubbler which will enable water form located in crop plants in rows and dense. Flow-diameter-length-hydraulic load curves were established. A sizing model was fitted to the irrigation system where feed tests were carried out in the field in different soil, to establish a model that relates flow rate, length of the irrigation bowl-time and eventually the installation of the irrigation system which evaluated the uniformity of flow in the area. The installation of the irrigation system was carried out in the municipality of Upanema / RN, in a Cambisol medium texture, cultivated with forage cactus using water supply Regarding the water breakthrough curves test soil, it can be said that the potential equations were similar logarithmic equations. It is recommended the use of potential model to represent the data of the water feed test on the ground curve. The prototype of the load losses virtually showed no change and were minimal, since the installed project this was very significant and with some variations. The project installed presented distribution uniformity coefficients (CUD) and statistical uniformity coefficient (CUE) with values ranging from good to excellent
Keywords: Déficit hídrico; Agricultura sustentável; Irrigação localizada; Bubbler; Water deficit; Sustainable agriculture; Drip irrigation; Efficiency; Bubbler; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO